Influence Compost Combined with Agroindustrial Waste on Soil Improvement, Paddy’s Growth, and Gas Emissions in Tidal Lands - Muhammad Helmy Abdillah (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2022)
The application of local organic matter is stated to be able to minimize biogeochemical constraints and increase rice yields but is a source of greenhouse gases in tidal mineral fields. Agroindustrial waste has the potential to be combined to reduce crude fiber from local organic matter. This study aims to compare the effect between materials of compost combined with agroindustry solid waste type that can improve soil properties, increase rice growth and reduce greenhouse gas emissions. This research was conducted at Polytechnic Hasnur’s greenhouse from November 2020 to July 2021 with a nested completely randomized design with Tukey’s HSD test a 5%.  The treatments in this study were rice straw compost, oil palm bunch compost, and purun rat compost, each of which was 253.7 g combined with 126.8 g of crumb rubber solid waste or 126.8 g of the solid decanter. There were 6 combinations and 1 control which was repeated 5 times to make 35 experimental units. The variables observed were plant height, number of productive tillers, root volume, percentage of pyrite, soil density, methane flux, and carbon dioxide. Application of 253.7 g of rice straw compost combined with 126.8 g of solid decanter increased plant height, decreased soil density, and CH4 flux at 60 and 90 days after planting (DAP). Application of 253.7 g of straw compost combined with 126.8 g of solid decanter increased the number of tillers, root volume, and decreased pyrite. The control treatment decreased CO2 flux at 30 and 90 DAP. Application of rat purun compost combined with crumb rubber solid waste was able to reduce CO2 flux 60 DAP.